“Fangs of blood”: oniric ethnographies of dreaming experiences in young Latin American residents of the Los Lagos region, Chile (2020-2023) - Saldivar Arellano, Juan M.; Márquez Reyes, Rodrigo E; Caldichoury Obando, Andrea N (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
The article presents pheniomenological reflections from some narrative-ethnographic findings on the experiences of dreaming among Latin Americans between the years 20202030 living in urban areas of the Los Lagos region, cities located in northern Patagonia of Chile, in order to understand the cultural dimensions of migrant life and its symbolic representations associated with the world of dreams. The proposed methodology is, at first, conceived from a mirror ethnography that dialogued with the interdisciplinary, especially in the development of participatory workshops, wich allowed the exploration of the object of study from the subjectivities as cultural practices that were narrated through of dense description. The results show how dream practices and dream experiences where subjects interpret their lived experiences were associated with the projection of migratory meanings around their stays, desires and demands in Chile. The contributions that this work makes to migration studies are, precisely, a new type of knowledge about the ways in which subjects relate and interact in anchor spaces where they project part of their experiences based on coping with new places of residence, representations that can be understood as meanings of nostalgia, nervous states and fears associated with the unknown.